Is it “impossible to will to be punished?” Exploring a consensual way out of the Kantian dilemma - Matías Parmigiani (Revista de Estudios Kantianos, 2017)
In the Metaphysics of Morals Kant wrote that “it is impossible to will to be punished”. The main goal of the present paper is to challenge this idea. In contemporary literature, a similar challenge was attempted by assigning a pivotal role to the notion of ‘consent’. Therefore, focused on these antecedents, what I will try to do in this paper is to determine whether the notion of consent is capable of playing any role whatsoever in a justificatory theory of punishment.